Peran Literasi Digital dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Zulaila, Ninik Azar; Purmadi, Ary (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The purpose of this study is to examine the role of digital literacy in improving the critical thinking skills of elementary school students. Digital literacy is a key competency in 21st century learning, because it relates to students' ability to access, understand, analyze, and evaluate information critically. This study uses the Systematic Literature Review (SLR) approach with reference to the PRISMA guidelines. The data source was obtained from Google Scholar and the Garuda Journal Portal, with the criteria for digital articles and books published in the 2018-2024 time frame, and focusing on digital literacy and critical thinking skills at the elementary school level. The selection and analysis process resulted in 20 relevant digital articles and books, which were analyzed based on the type of digital literacy intervention, learning strategies, and their impact on students' critical thinking skills. The results of the study show that digital literacy consistently contributes to improving the high level of cognitive abilities, analytical skills, and problem-solving abilities of elementary school students, especially when integrated through the use of interactive digital learning media and problem-solving-based learning strategies. The findings of this study confirm that strengthening digital literacy not only functions as a learning support, but also as a strategic factor in the development of critical thinking skills of elementary school students. Thus, the results of this study make a conceptual contribution to the development of digital literacy-based learning, as well as a reference for educators and policy makers in designing learning that is oriented towards critical thinking skills.